MOTIVASI DEFINISI INVERS MOORE PENROSE PADA RING DENGAN ELEMEN SATUAN YANG DILENGKAPI INVOLUSI - SRRM, Titi Udjiani (MATEMATIKA, 2016)
Development on the research of the inverse matrix until the Moore Penrose inverse matrix motivate researchers to conduct the research on the Moore Penrose inverse and the inverse of element in the ring with a unit element. The used method is expanding the definition of inverse in matrix to the ring with a unit element. Also generalizing the transpose operation of matrix to be a function of involution on the ring.